(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2017)
Background: The STarT Back Screening Tool (SBST) is used to classify patients with low back pain (LBP) into three risk categories of having a poor prognosis. However baseline classification does not take into account variables that can influence the prognosis during treatment or over time. Objectives: This study was designed to investigate what is the best time to using SBST to predict clinical outcomes. Specifically, we investigated (1) the changes in the risk classification measured by the SBST over a period of 6 months and (2) the long-term predictive ability of the SBST when applied at different time points in patients with chronic LBP who receive physical therapy treatment. Methods: A 6-month prospective cohort study nested into an existing randomised controlled trial. This study was approved by the Ethics Committee (CAAE 14386513.4.0000.0064). Were included 148 patients with chronic nonspecific LBP, of both genders, aged between 18 and 80 years and who were seeking physiotherapy treatment. Clinical outcomes of pain intensity, disability and global perceived effect as well as SBST were collected at baseline, after 5 weeks, 3 and 6 months. All patients received 10 sessions of physiotherapy, including general and specific exercises for the lum¬bar spine and manual therapy techniques. Three categories were created to evaluate the changes in the SBST subgroups (improved, worsened, stable). Changes in SBST subgroups were calculated using descriptive statistics. Linear regression models were build to analyze the predictive ability of SBST when applied at different points of time. Results: After receiving good quality physiotherapy care, 60.8% changed their risk classification (54.7% improved the risk). The subgroup with the highest percentage of change (75%) was the medium risk. The SBST improved the prediction of disability, pain intensity and global perceived effect at 5 weeks, 3 months and changes from 5 weeks to baseline, after controlling for potential confounders. The SBST at baseline did not improve the predictive ability of the models after adjusting for confounding. Conclusions: This study shows that many patients change their risk subgroup after received physiotherapy care. The predictive ability of the SBST in patients with chronic LBP increases when applied in different time points, especially after treatment. Key words: assessment, low back pain, prognosis, STarT Back Screening Tool.